DETERMINATION OF REACTIVE HBsAg CUT-OFF THAT NEED CONFIRMATORY TEST - Sherly Purnamawaty; Irda Handayani; Asvin Nurulita; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Hepatitis B surface antigen (HBsAg) is the earliest and most important serological marker for the diagnosis of HBV infection. The availability of new methods with a high sensitivity to detect HBsAg results in the increase of false reactive results so that a confirmatory test is needed,but this will increase the total test cost. A reactive cut-off value for a confirmatory test is needed to make the use of this test more efficient. This study was a cross-sectional. All the specimens with HBsAg >0.17 Cut-Off Index (COI) were confirmed with HBsAg confirmatory test. HBsAg test used a sandwich ELFA method while HBsAg confirmatory test used an antibody neutralization method. Analysis of the ROC curve obtained HBsAg cut-off value that need confirmatory test. Total samples were 80 with 51 (63.8%) confirmed reactive and 29 (36.2%) non-reactive. There was a statistically significant difference between HBsAg that confirmed reactive (median 2.76 COI) and non-reactive (median 0.32 COI) (p<0.001). ROC curve showed an AUC of 0.805 which meant a good diagnostic performance for HBsAg test based on a confirmatory test. The specificity of 89.66% and sensitivity 64.71% were obtained from the cut-off 1.08 COI and considered the best cut-off. Some possible causes of false reactive results were Hepatitis B vaccine, G-CSF therapy and limitation of the HBsAg methods. HBsAg cut-off with ELFA method that need HBsAg confirmatory test was <1.08 COI. The researchers suggests further studies with different sampling methods so a better data distribution can be obtained.